2000
DOI: 10.2514/2.1008
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Generated Localized Freestream Perturbations in Supersonic and Hypersonic Flows

Abstract: An optical method for generating localized, controlled perturbations has been developed for use in supersonic and hypersonic ow elds. The thermal spot disturbance is generated when the pulsed beam from a laser is focused at the desired origin and a small region of the gas is ionized. After recombination, the thermal spot persists as a region of heated gas that convects with the local ow velocity. The perturbation is approximately spherical and several millimeters in diameter, with the size dependent on the ow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Schmisseur et al [12,13] studied the receptivity of a freestream laser spot over an elliptical cone in a Mach 4 flow. Salyer et al [14,15] characterized the laser-generated hotspot and used it in a boundary-layer receptivity experiment for a hemisphere-cylinder model in Mach 4 freestream.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Schmisseur et al [12,13] studied the receptivity of a freestream laser spot over an elliptical cone in a Mach 4 flow. Salyer et al [14,15] characterized the laser-generated hotspot and used it in a boundary-layer receptivity experiment for a hemisphere-cylinder model in Mach 4 freestream.…”
mentioning
confidence: 99%
“…The schematic explanation of the laserspot and cone setup in the experimental studies is demonstrated in Fig. 1 [12,13]. The hotspot is initially generated at a location upstream from the cone on the centerline.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This thermal disturbance is surrounded by a weak spherical shock propagating at the speed of sound away from the core [24,25]. More information on this apparatus can be found in [26][27][28].…”
Section: Laser Perturbermentioning
confidence: 99%